2015
DOI: 10.1016/j.jmb.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Roles of BamA, BamB and BamD in the Biogenesis of BamA, a Core Protein of the β-Barrel Assembly Machine of Escherichia coli

Abstract: Assembly of the β-barrel outer membrane proteins (OMPs) is an essential cellular process in Gram negative bacteria and in the mitochondria and chloroplasts of eukaryotes—two organelles of bacterial origin. Central to this process is the conserved β-barrel OMP that belongs to the Omp85 superfamily. In Escherichia coli, BamA is the core β-barrel OMP, and together with four outer membrane lipoproteins, BamBCDE, constitute the β-barrel assembly machine (BAM). In this paper, we investigated the roles of BamD, an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 56 publications
(150 reference statements)
1
41
0
Order By: Relevance
“…These barrel and eL6 altering mutations, essentially confer a gain of function phenotype bypassing the requirement for BamA communication with the periplasmic lipoproteins. One of the mutations, bamA_F494L , was later shown to also be a partial bypass suppressor of bamD (63). Although bamD is still essential, it can be almost completely depleted in bamA_F494L strain without affecting viability (63).…”
Section: Models For the β-Barrel Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…These barrel and eL6 altering mutations, essentially confer a gain of function phenotype bypassing the requirement for BamA communication with the periplasmic lipoproteins. One of the mutations, bamA_F494L , was later shown to also be a partial bypass suppressor of bamD (63). Although bamD is still essential, it can be almost completely depleted in bamA_F494L strain without affecting viability (63).…”
Section: Models For the β-Barrel Assemblymentioning
confidence: 99%
“…One of the mutations, bamA_F494L , was later shown to also be a partial bypass suppressor of bamD (63). Although bamD is still essential, it can be almost completely depleted in bamA_F494L strain without affecting viability (63). …”
Section: Models For the β-Barrel Assemblymentioning
confidence: 99%
“…Intriguingly, BamA might prove an example of pathway crossover. How BamA reaches the OM is unknown, but both the BAMlipoproteins BamA associates with [52,53] and BamA itself [2] are suggested to help BamA assembly. Further research should establish whether some or all of these OMPs truly are substrates with mixed BAM-and Lol-dependence or whether some observations require revalidation by independent approaches to rule out erroneous interpretations resulting from the complexity of the in vivo experimental systems used.…”
Section: Signs Of Pathway Crossover?mentioning
confidence: 99%
“…They facilitate the insertion of β‐barrel‐shaped proteins into the OM of Gram‐negative bacteria, mitochondria, their descendent organelles, and probably even in chloroplasts . The best studied prokaryotic Omp85 protein is BamA (β‐barrel assembly machinery protein A) in Escherichia coli , which together with the lipoproteins BamB, C, D, and E facilitate the insertion of other β‐barrel‐shaped OM proteins . Structural analysis of BamA confirmed that the protein consists of five N‐terminal polypeptide transport‐associated (POTRA) domains and the C‐terminal 16‐stranded pore‐forming β‐barrel domain that is characteristic for all Omp85 proteins .…”
Section: Introductionmentioning
confidence: 99%